2021
DOI: 10.3390/polym13152553
|View full text |Cite
|
Sign up to set email alerts
|

Halogen-Free Flame Retardant Polypropylene Fibers with Modified Intumescent Flame Retardant: Preparation, Characterization, Properties and Mode of Action

Abstract: A novel intumescent flame retardant (IFR) agent designated as Dohor-6000A has been used to prepare halogen-free flame retardant polypropylene (PP) fibers via melting spinning. Before being blended with PP resin, a surface modification of Dohor-6000A was carried out to improve its compatibility with the PP matrix. The rheological behavior of flame retardant Dohor-6000A/PP resin, the structure, morphology, mechanical properties, flammability of the Dohor-6000A/PP fibers were studied in detail, as well as the act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…Neat TPE is a block copolymer with hard blocks and soft blocks as repeating units in the main chain. Relatively high plastic processing performances, good aging resistance, tensile strength and friction resistance were given to the material by the hard blocks; and the soft blocks make TPE more flexible and amorphous, showing excellent tensile strain, flexural properties and high resilience [1][2][3]. TPE combining the advantages of the flexibility of rubbers, the strength of plastics and the processability of thermoplastics, has been widely used in furniture, footwear, ideal cable sheathing layers, insulation materials, coatings, adhesives and elastomers.…”
Section: Introductionmentioning
confidence: 99%
“…Neat TPE is a block copolymer with hard blocks and soft blocks as repeating units in the main chain. Relatively high plastic processing performances, good aging resistance, tensile strength and friction resistance were given to the material by the hard blocks; and the soft blocks make TPE more flexible and amorphous, showing excellent tensile strain, flexural properties and high resilience [1][2][3]. TPE combining the advantages of the flexibility of rubbers, the strength of plastics and the processability of thermoplastics, has been widely used in furniture, footwear, ideal cable sheathing layers, insulation materials, coatings, adhesives and elastomers.…”
Section: Introductionmentioning
confidence: 99%
“…It is also worth noting that a reduction in the mass fraction of PP in the composite has an impact on crystallinity. Therefore, the crystallinity of the composites could be calculated by considering the mass fraction of the polymer matrix in the composites 66–69 . The degree of crystallinity plays a pivotal role in determining the mechanical properties of composites.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the crystallinity of the composites could be calculated by considering the mass fraction of the polymer matrix in the composites. [66][67][68][69] The degree of crystallinity plays a pivotal role in determining the mechanical properties of composites. Specifically, the mechanical properties of semi-crystalline polymers like PP are closely tied to their crystallinity.…”
Section: Dsc Analyses Resultsmentioning
confidence: 99%
“…The combustion behaviour of PP composites was analysed using MCC tests. Some important parameters, such as the specific HRR, total heat release (THR) and temperature of peak HRR (T pHRR ), could be obtained from MCC tests [21,39]. The corresponding data are summarized in Table 2.…”
Section: Flame Retardancy Of Pp Compositesmentioning
confidence: 99%
“…After introducing 1-7 wt% OMMT, the TpHRR value remained within 477.2-485.1 °C. The increase in TpHRR value indicated that PP/PN-DOPO/OMMT composites were more difficult to burn than PP and PP/PN-DOPO and could delay the decomposition process of the matrix [39], which enhances the flame retardancy of PP.…”
Section: Flame Retardancy Of Pp Compositesmentioning
confidence: 99%